Case report Fatal stroke in a young cocaine drug addict: chemical hair analysis and cervical artery examination twenty months after death - De Giorgio, Fabio; Vetrugno, Giuseppe; Fucci, Nadia; Rainio, Juha; Tartaglione, Tommaso; Di Lazzaro, Vincenzo; Carbone, Arnaldo (Folia Neuropathologica, 2007)
We present a case of a 26-year-old female who died of acute cerebral infarction after thrombosis of the left internal carotid artery, conceivably related to cocaine use. The forensic examination was performed only twenty months post-mortem. Revaluation of clinical data was carried out after exhumation and forensic autopsy examination were done, including anatomic dissection of cervical vessels and histological and toxicological analyses. Interestingly, comparative histological examination of cervical arteries was more useful in determining the putative site of vascular damage than gross and histological examination of the brain itself, although the state of preservation of tissues was poor. In conclusion, when a vascular accident is suspected or has to be demonstrated, we suggest performing comparative histological examinations of selected artery samples, even several months after death.